Tales from the totems of the Hidery [electronic resource] - Deans, James; Triggs, Oscar Lovell, 1865-1930. (Chicago : [s.n.], 1899)
Original published in series: Archives of the International Folk-lore Association, Vol. II Electronic reproduction. Mode of access: Internet. 44